Bartonella bovis and Candidatus Bartonella davousti in cattle from Senegal. (February 2017) - Dahmani, Mustapha; Sambou, Masse; Scandola, Pierre; Raoult, Didier; Fenollar, Florence; Mediannikov, Oleg
Highlights: Bartonellosis in animals from Senegal. Culture of Bartonella species from cattle. Prevalence and genetic diversity of the Bartonellae in cattle in Senegal. Description of new species of Bartonella from cattle. Abstract: In Senegal, domestic ruminants play a vital role in the economy and agriculture and as a food source for people. Bartonellosis in animals is a neglected disease in the tropical regions, and little information is available about the occurrence of this disease in African ruminants. Human bartonellosis due to Bartonella quintana has been previously reported in Senegal. In this study, 199 domestic ruminants, including 104 cattle, 43 sheep, and 52 goats were sampled in villages from the Senegalese regions of Sine Saloum and Casamance. We isolated 29 Bartonella strains, all exclusively from cattle. Molecular and genetic characterization of isolated strains identified 27 strains as Bartonella bovis and two strains as potentially new species. The strains described here represent the first Bartonella strains isolated from domestic ruminants in Senegal and the first putative new Bartonella sp. isolated from cattle in Africa.